Crossability analysis of cultivated rice (Oryza sativa) with O. rufipogon and O. longistaminata and F1-identification - CHAKRAWARTI, NEHA; BORGOHAIN, RUPAM; VERMA, RAJSHREE; BARUA, N SARMA (The Indian Journal of Agricultural Sciences, 2023)
The research was conducted at Instructional cum Research (ICR) farm in Assam Agricultural University, Jorhat, Assam for the year 2019–21 with the objective to determine the crossability of wild rice species O. longistaminata and O. rufipogon with O. sativa and observe the inheritance of rhizome. In first year of experiment, varieties having good ratooning ability were identified. Out of them, five varieties namely Ranjit, Ranjit sub-1, IR-64, Binadhan-11 and Bahadur were crossed with both of the wild species. Crossablity of O. longistaminata with O. sativa ranged from 11.1% (Ranjit sub-1 × O. longistaminata) to 22.2% (Binadhan11 × O. longistaminata) while O. rufipogon with O. sativa ranged from 13.3% (Ranjit sub-1 × O. rufipogon) to 30% (Ranjit × O. rufipogon). All the hybrids except for IR64 × O. longistaminata were photoinsensitive as that of their female parent. Hybrids from O. sativa/O. longistaminata exhibited various distinguishing characters which can be used as morphological marker in order to identify true interspecific hybrids in further breeding programme. The pollen viability of these interspecific hybrids were found lower than both the parents. However, rhizome formation could not be observed in any hybrid.